ln(x/2)^3-ln(y/2)^3=3ln(x/2)-3ln(y/2)=3ln[(x/2)/(y/2)]=3ln(x/y)=3(lnx-lny)=3a
若lnx-lny=a,则ln(x/2)^3-ln(y/2)^3等于?
1个回答
相关问题
-
ln(x+y)=?lnx+lny=?
-
lnx-lny等于ln(x/y)吗
-
若x∈(e^-1,1).a=lnx,b=2lnx,c=ln^3 x 为什么a-b=-lnx>0,a-c=lnx(1-ln
-
怎么证明 lnx +lny =ln xy
-
已知 y=(8x+4)^(4x+4) 求y' 1)lny=ln( ) 2)lny=( ){化简} 3) y'/y=( )
-
已知 y=(8x+4)^(4x+4) 求y' 1)lny=ln( ) 2)lny=( ){化简} 3) y'/y=( )
-
解关于x的方程:ln(x^2+1)-3lnx=ln2,
-
设f(x)=lnx,若f'(x0)=2,则x0=?A、e² B、e C、ln2/2 D、ln2
-
,谢谢y=(2 ln x + x^2)/(3lnx + x^2)求导过程?
-
log(3,2)=a=ln2/ln3 ln2/ln3 ln是什么